Assessment of DNA damage in welders using comet and micronucleus assays - Aksu, Ildeniz; Anlar, Hatice Gul; Taner, Gökçe; Bacanli, Merve; Iritas, Servet; Tutkun, Engin (Elsevier, 2019)
Welding technology is widely used in pressurized containers, thermal power plants, refineries, chemical facilities and steel structures. Welders are exposed to a number of hazardous compounds such as ultraviolet (UV) radiation, electromagnetic fields, toxic metals and polycyclic aromatic hydrocarbons (PAHs). In the present study, 48 welders and an equal number of control subjects were evaluated for DNA damage in the whole blood and isolated lymphocytes using the comet assay. The genotoxic damage in buccal epithelial cells of subjects was determined by micronucleus (MN) assay. Metal(loids) such as Cr, Mn, Ni, Cu, As, Cd and Pb levels in blood samples were evaluated by using Inductively Coupled Plasma-Mass Spectrometer (ICP-MS). Results of this study showed that DNA damage in blood, isolated lymphocytes, and buccal epithelial cells were significantly higher in workers compared to the controls. Also, these workers had remarkably higher blood Cr, Cu, Cd, Ni and Pb levels. These results showed that occupational exposure to welding fumes may cause genotoxic damage that can lead to important health problems in the workers. More extensive epidemiological studies should be performed that enable the assessment of health risk in welding industry.
Keywords: Welders; Welding fumes; Alkaline single cell gel electrophoresis; Buccal micronucleus cytome assay; Inductively coupled plasma-mass spectrometer